1984
DOI: 10.1111/j.1600-0536.1984.tb00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Stevens‐Johnson syndrome associated with occupational exposure to trichloroethylene

Abstract: Reports on cases of Stevens-Johnson syndrome (erythema multiforme major) have seldom related it to occupational exposure to chemicals. Serious liver involvement is also uncommon. This report describes 5 cases of the syndrome who had been occupationally exposed to trichloroethylene. The circumstantial evidence suggested that the chemical might have been a causative factor in the disease. The liver was involved in all and in 3 it was serious, with one death. The degree of exposure to trichloroethylene varied. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
44
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(47 citation statements)
references
References 17 publications
3
44
0
Order By: Relevance
“…Environmental and occupational exposure to TCE has been linked to the development of autoimmune diseases, such as systemic lupus erythematosus (SLE), scleroderma, systemic sclerosis, and fasciitis (Lagakos et al, 1986;Byers et al, 1988;Kilburn and Warshaw, 1992;Waller et al, 1994;Reinl, 1957;Saihan et al, 1978;Phoon et al, 1984;Flindt-Hansen and Isager, 1987;Lockey et al, 1987;Brasington and Thorpe-Swenson, 1991;Goon et al, 2001;Brautbar, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Environmental and occupational exposure to TCE has been linked to the development of autoimmune diseases, such as systemic lupus erythematosus (SLE), scleroderma, systemic sclerosis, and fasciitis (Lagakos et al, 1986;Byers et al, 1988;Kilburn and Warshaw, 1992;Waller et al, 1994;Reinl, 1957;Saihan et al, 1978;Phoon et al, 1984;Flindt-Hansen and Isager, 1987;Lockey et al, 1987;Brasington and Thorpe-Swenson, 1991;Goon et al, 2001;Brautbar, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Only one patient (case 3) had developed hepatitis, as determined by increased aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), and bilirubin levels. 4) Phoon et al 4) Phoon et al 4) Phoon et al 4) Rabens 6) Rabens 6) Rabens 6) Rabens 6) Phoon et al 4) reported five cases. Cases 5 and 6 were twin sisters who had worked in the same factory.…”
Section: Clinical Manifestation Of Trichloroethylene-related Generalimentioning
confidence: 99%
“…Together with anesthetic action, hepatic damage, polyneuropathy, trigeminal neuropathy, and dermatitis with skin irritation are familiar diseases which occur as a result of exposure 1,2) . In addition to the non-specific skin irritation resulting by the defatting action, severer generalized dermatitis with hepatitis, which includes Stevens-Johnson syndrome and toxic epidermal necrolysis, sometimes occurs after exposure to trichloroethylene [3][4][5][6][7][8][9][10] . Such dermatitis is generally known to occur subsequent to the administration of various medicines and infections-i.e., antibiotics such as sulfonamides, anticonvulsives such as carbamazepine and phenobarbital, anti-inflammatory medications such as acetylsalicylic acid and paracetamol, anti-parasitic medications such as albendazole and tinidazole, viruses, mycoplasma, and other bacterial infections [11][12][13][14][15] .…”
mentioning
confidence: 99%
“…The disorders are not caused solely by drugs. A close link between occupational solvent exposure, mostly trichloroethylene (TCE), and severe generalized skin disorders has been suggested by a series of case reports [3][4][5][6][7][8][9][10][11] . Recently, the number of patients suffering from TCE-related severe skin disorders has been increasing in Asia, especially the Philippines, Singapore, Taiwan and Guangdong Province, China 10,12,13) .…”
mentioning
confidence: 99%